FUSI GEN BREAKPOINT CLUSTER REGION ABELSON KINASE (BCRABL) DAN UJI HEMATOLOGIS RUTIN - Delita Prihatni; Ida Parwati; Rahmat Sumantri; Rully MA. Roesli; Nurizzatun Nafsi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Chronic myeloid leukemia (CML) is a type of Chronic myeloproliferative disorders in pluripotencial stem cell haematopoiesis cell disease caused by somatic mutation chromosomal translocation of the Abelson (ABL) and Breakpoint Cluster Region (BCR) genes on chromosomes 9 and 22. The Breakpoint Cluster Region Abelson Kinase (BCR-ABL) gene encodes different fusion transcripts of messenger Ribo Nucleic acid (m RNA)/type of fusion gene that vary in size depending on the breakpoint in the BCR gene. The majority of CMLcases have been shown to have either b3a2 or b2a2 fusion gene. This research is a preliminary study designed to know how to identify a quantification BCR-ABL gene and expression fusion of gene and its relation to routine haematological parameters. The researchers analyzed 12 adults who were positive using a quantification ratio BCR-ABL and Glucose-6-Phosphate Dehydrogenase (G6PDH) as a house keeping gene by real-time quantitative polymerase chain reaction (RQ PCR) of chronic phase of CML patients, qualitative of translocation of BCR-ABL gene by gel agarose and routine haematological tests by a haematologic analyzer. The average quantification ratio of BCRABL gene and G6PDH was 0.0881, 50% patients had b3a2 fusion gene, 41.6% had b2a2 dan 0.4% had e1a1. Fusion gene b3a2 showed a quantification ratio, haemoglobin level and leukocyte count higher compared to b2a2 fusion gene.